How Brand Community Contribute To WOM And Loyalty : Evidence From Railfans Community - Silvia Van Marsally; Refius Pradipta Setyanto; Agapito Barros (Faculty of Economics and Business Universitas Jenderal Soedirman, 2023)
Today's brand community is not only a marketing medium for companies, but also a long-term business strategy to maintain the existence of a brand. Brand community strategies tend to be found in products owned by consumers directly such as ownership of motorized vehicles, automotive, mobile phones, and electronic devices. However, there are also service companies that implement brand community strategies, one of which is PT. Indonesian Railroad (Persero). This study aims to analyze the influence of the brand community on word of mouth and loyalty to the Railfans community of PT. Kereta Api Indonesia (Persero) in the Central Java Region. This research is a type of quantitative research using a survey method using a questionnaire given to Railfans members in the Central Java region. Sampling was determined using the purposive sampling method, with a total of 130 Railfans members. The data obtained were analyzed descriptively and using the AMOS Structural Equation Model (AMOS SEM). The results showed that to increase word of mouth and loyalty, PT. Kereta Api Indonesia (Persero) is expected to increase the participation of its community members first. As an effort to increase participation, two things need attention, namely increasing member satisfaction and community-brand member relations.